Childhood environment and adult height among Polish university students - Wronka, Iwona (Array, 2009)
Abstract: The objective of the study is to assess whether the choice of a childcare type (i.e. a mother giving up a professional career to take care of her child, employing a childminder, day care centre and kindergarten) depends on a child’s family socio-economic status and to investigate whether the childcare type affects an adult’s height. The material for the study was gathered in the cross-section research carried out among 783 female students and 535 male students of universities in Krakow and Opole (southern Poland). The height was measured with standard anthropometric instruments. To assess a socio-economic status (SES), the following factors were analysed: a place of living before entering the university, the educational background of parents and a self-assessment of their material situation. It was found that students from families with a high socio-economic status attended crčches and kindergartens much more frequently than others of the same age, while those who grew up at home under their mothers’ care, most frequently come from families with a lower socio-economic status. A socio-economic status does not significantly affect body heights of the researched sample group, however, students from high socio-economic status families are slightly taller than their peers. Females and males who spent their childhood under the care of their non-working mothers are the tallest, whereas those who attended crčche and kindergarten are the shortest. After the students to be examined were divided into three groups with low, average and high statuses respectively, it was observed that in every group the persons who spent their childhood under the care of their non-working mothers are taller than the ones who attended crčche and kindergarten